The Roman Empire economy, society and culture - Garnsey, Peter 1938-; Saller, Richard P. 1952- (Duckworth, 1987)
"During the first, stable period of the Principate (roughly from 27 BC to AD 235), when the empire reached its maximum extent, Roman society and culture were radically transformed. But how was the vast territory of the empire controlled? Did the demands of central government stimulate economic growth, or endanger survival? What forces of cohesion operated to balance the social and economic inequalities and high mortality rates? Why did Roman governments freeze the official religion while allowing the diffusion of alien, especially oriental, cults? Are we to see in their attitude to Christianity a policy of toleration - or simply confusion and a failure of nerve? These are some of the many questions posed in this book, which offers the first overall account of the society, economy and culture of the Roman empire. Addressed to non-specialist readers no less than to scholars, it breaks with the traditional historian's preoccupation with narrative and politics. As an integrated study of the life and outlook of the ordinary inhabitants of the Roman world, it deepens our understanding of the underlying factors in this important formative period of world history." -- Book cover.
Literaturverz. S. 204 - 224
Keywords: Geschichte 27 v. Chr.-235; Alltag, Brauchtum; Geschichte; Historia Antiga - Roma (Povos); Sociaal-economische geschiedenis; Wirtschaft; Sozialgeschichte; Gesellschaft; Kultur; Rom; Rome - 30 av. J.-C.-284; Rome - Conditions sociales; Rome - Conditions économiques; Rome - Histoire - 30 av. J.-C.-284 (Empire); Rome - Murs et coutumes; Rome - Social life and customs; Rome -- Economic conditions -- Empire, 30 B.C.-284 A.D; Rome -- History -- Empire, 30 B.C.-284 A.D; Rome -- Social conditions -- Empire, 30 B.C.-284 A.D; Rome -- Social life and customs -- Empire, 30 B.C.-284 A.D; Römisches Reich